1998
DOI: 10.1111/1467-9507.00050
|View full text |Cite
|
Sign up to set email alerts
|

Infants Protest Their Mothers’ Attending to an Infant‐Size Doll

Abstract: Twelve-month old infants (N ϭ 76) experienced 4 situations of unresponsiveness in which their mothers and a stranger directed positive attention toward a doll or a picture book while they ignored the infant. Infants demonstrated more protest, negative vocalizations and inhibited play during the doll condition, particularly if the doll was held by the mother. Infant contacts with the mother were more frequent when the mother held the doll. Infants' distress during the mother/doll condition was interpreted as je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
92
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(105 citation statements)
references
References 8 publications
9
92
1
Order By: Relevance
“…Their findings were ambiguous, with even 'excluded' babies being interested in both partners, not just the adult as predicted. Another type of triangular study has been done by Hart and colleagues [Hart, Field, & Del Valle 1998a;Hart, Field, Letourneau, & Del Valle 1998b], who 204 Human Development 200346:197-221 Selby/Bradley showed that infants protest more when their mothers direct attention to a life-size doll than to a book (i.e. betokening 'jealousy').…”
Section: Previous Research On Babies With Peersmentioning
confidence: 99%
“…Their findings were ambiguous, with even 'excluded' babies being interested in both partners, not just the adult as predicted. Another type of triangular study has been done by Hart and colleagues [Hart, Field, & Del Valle 1998a;Hart, Field, Letourneau, & Del Valle 1998b], who 204 Human Development 200346:197-221 Selby/Bradley showed that infants protest more when their mothers direct attention to a life-size doll than to a book (i.e. betokening 'jealousy').…”
Section: Previous Research On Babies With Peersmentioning
confidence: 99%
“…Consistent with this idea, Hart et al (1998a) mention that some 12-month-olds aggressed toward the rival doll to whom the mother was exclusively attending. Nevertheless, infants' anger has been shown to have directedness from 4 months of age and perhaps even earlier (Sternberg & Campos, 1990), demonstrating that it may be possible to determine the target of jealous anger in the first third of a year of life.…”
Section: The Behavioral Modes Of Jealousymentioning
confidence: 79%
“…Behaviors of hitting, pinching, or tugging a loved one would be more demonstrative of jealous hostility. Many studies report that infants touch their parent more in jealous contexts (Hart, Field, del Valle, & Letourneau, 1998a;Hart, Field, Letourneau, & del Valle, 1998b). However, these studies do not describe and differentiate what type of touching this is, as a gentle tug on the mother's blouse is very different from striking out at her arm.…”
Section: The Behavioral Modes Of Jealousymentioning
confidence: 99%
See 1 more Smart Citation
“…However, support for this prediction is lacking. In fact, it is markedly absent in research on experimentally induced jealousy (Draghi-Lorenz, 1998;Hart, this volume, Chapter 4;Hart & Carrington, 2002;Hart, Field, del Valle, & Letourneau, 1998a;Masciuch & Kienapple, 1993), in which the object of maternal attention is manipulated (see Chapter 4 for more detail on jealousy evocation) and in which mothers generally had not been pregnant, and so these children had not been systematically exposed to maternal separation or diminished quality of mother-child interactions. Nonetheless, they were most upset when the object of their mothers' attention was another child.…”
mentioning
confidence: 99%